Lobaplatin-Induced Apoptosis Requires p53-Mediated p38MAPK Activation Through ROS Generation in Non-Small-Cell Lung Cancer - Zhang, Hongming; Chen, Runzhe; Wang, Xiyong; Zhang, Haijun; Zhu, Xiaoli; Chen, Jibei (Frontiers in Oncology, 2019)
Lung cancer is the leading cause of cancer-related death worldwide. Platinum-based chemotherapy is recommended as the first-line treatment regimen for patients with advanced non-small-cell lung cancer. Lobaplatin, a third-generation platinum anti-neoplastic agent, has shown an improved efficacy against lung cancer. This study aimed to investigate the mechanisms of LBP-induced apoptosis in the A549 p53 wild-type cell line. The Cell Counting Kit-8 assay, flow cytometry, Western blotting, xenograft tumour models, terminal deoxynucleotide transferase dUTP nick end labelling and RNA interference were used in this study. LBP can inhibit the proliferation of A549 cells. At lower concentrations, LBP triggers cell cycle arrest at the G1 phase in A549 cells. LBP can also induce apoptosis in A549 cells. LBP increased the expression of PARP and Bax and the cleavage of caspase-3, caspase-8, and caspase-9 and reduced Bcl-2 expression. In vivo experiment confirmed that LBP can inhibit tumour growth in the A549 xenograft models, and induce apoptosis. The sensitivity of A549/p53-shRNA to LBP was affected when wild-type p53 was silenced. When A549 cells were transfected with p53 shRNA or treated with NAC and SB203580, the pro-apoptotic effect of LBP was inhibited. The study shows that the p53/ROS/p38MAPK pathway appeared to mediate the LBP-induced apoptosis of A549 cells, suggesting that LBP is a promising candidate for the treatment of NSCLC with wild-type p53.